Emotions in Korean philosophy and religion: confucian, comparative, and contemporary perspectives - Chung, Edward Y. J.; Oh, Jea Sophia (Palgrave Studies in Comparative East-West Philosophy, 2022)
Chapter 1. Introduction: “Emotions (Jeong/Qing 情) in Korean Philosophy and Religion” -- Chapter 2. Moral Psychology of Emotion in Korean Neo-Confucianism and Its Philosophical Debates on the Affective Nature of the Mind -- Chapter 3. The Idea of Gyeong/Jing 敬 in Yi Toegye’s Korean Neo-Confucianism and Its Availability in Contemporary Ethical Debate -- Chapter 4. “Yi Yulgok on the Role of Emotions in Self-Cultivation and Ethics: A Modern Korean Neo-Confucian Interpretation”.-Chapter 5. Dasan Jeong Yagyong on Emotions and the Pursuit of Sagehood -- Chapter 6. Thinking through the Emotions with Korean Confucianism: Philosophical Translation and The Four-Seven Debate -- Chapter 7. Jeong (情), Civility, and the Heart of a Pluralistic Democracy in Korea -- Chapter 8. Korean Social Emotions: Han (한 恨), Heung (흥 興), and Jeong (정 情) -- Chapter 9. Hanmaeum, One Heart-Mind A Korean Buddhist Philosophical Basis of Jeong (情) -- Chapter 10. Resentment and Gratitude in Won Buddhism -- Chapter 11. Jeong and the Interrelationality of Self and Other in Korean Buddhist Cinema -- Chapter 12. Emotions (Jeong 情) in Korean Confucianism and Family Experience An Ecofeminist Perspective -- Chapter 13. CONCLUSION: The Diversity, Dynamics, and Distinctiveness of Korean Jeong.